Engineering Student’s Issues in Internship Training - NAVIN GARG, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Nowadays, finding a job is by no means simple. The employer has higher standards for the workers. Today, a large number of graduates, particularly engineers, are jobless due to a lack of work experience. Hence, internships fill the gap and aid in turning graduates into workers by giving them practical work experience. The main goal of this study is to pinpoint the difficulties engineering students from particular engineering colleges in Solan district of Himachal Pradesh encounter throughout their internship training programmes. To determine the students for the current study, the researcher used the convenience sampling approach. All these primary and secondary data have been utilized in the study. Again for study, the researcher utilized a different statistical tools for analyzing the data. The study's main findings were that the majority of respondents had trouble with their internships' short durations and were reluctant to ask concerns.